Volatiles of the Predator Xylocoris flavipes Recognized by Its Prey Tribolium castaneum (Herbst) and Oryzaephilus surinamensis (Linne) as Escape Signals - Shaohua Lu; Li Yang; Zonglin Wu; Mingshun Chen; Yujie Lu (Insects)
The olfactory sensory system plays vital roles in daily activities, such as locating mate partners, foraging, and risk avoidance. Natural enemies can locate their prey through characteristic volatiles. However, little is known about whether prey can recognize the volatiles of their predators and if this recognition can increase the efficiency of prey escaping from predators. Xylocoris flavipes is a predator of Tribolium castaneum (Herbst) and Oryzaephilus surinamensis (Linne) that has been widely used in stored pest control. Herein, we analyze the volatile components of Xylocoris flavipes and their impacts on the olfactory behavior of T. castaneum and O. surinamensis. We found that T. castaneum and O. surinamensis preferred blank air rather than odors of X. flavipes and X. flavipes emissions, which significantly decreased the orientation preference of T. castaneum and O. surinamensis to wheat. X. flavipes emits three major volatiles, including linalool, α-terpineol, and geraniol. Y-tube bioassays showed that T. castaneum and O. surinamensis can recognize linalool and geraniol at certain concentrations, especially at 200 μg/mL. EAG recordings verified that linalool and geraniol elicit higher olfactory responses in the two pests, but very small EAG responses were observed in the insects to α-terpineol. A further repellency evaluation also proved that linalool and geraniol are repellent to the two pests, and this repellency can be slightly enhanced by mixing them together. T. castaneum and O. surinamensis can recognize the predator X. flavipes by perceiving its volatiles and using them as signals for escaping. The two most potent volatiles, linalool and geraniol, may have potential values as repellents in controlling pests in these two stored products.